Multiband dual polarized OFDM signal: generation and distribution over fiber - Amiri, I. S.; Ariannejad, M. M.; Zulkifli, Mohd Zamani; Ahmad, H. Ahmad (Elsevier GmbH, 2017)
Microring Resonator (MRR) system is utilized to generate comb signal including eight carriers, owing 10 GHz free spectral range (FSR) to be applied in wavelength-division multiplexing (WDM) systems. Applying multiband (MB) approach, the ultra-high spectral effective orthogonal frequency-division multiplexing (OFDM) technology is utilized to modulate each of the simulated multicarrier and by taking advantage of the dual polarization (DP) technique the high data rate of 236.8 Gb/s MBDP-OFDM signal is achieved. The MB-DP-OFDM signal is transmitted through 50 km single mode fiber (SMF) and received by the coherent receiver. The system’s performance was assessed by using the bit error rate (BER) of the system, where the BER of 2×10-3 was achieved.